A new species of Metabelbella (Acari: Oribatida: Damaeidae) from Quercus forests of southern Portugal - Ermilov, Sergey G.; Shtanchaeva, Umukusum Y.; Subías, Luis S. (International Journal of Acarology, 2012)
In the course of studies of the oribatid fauna of oak forests from southern Portugal, we found representatives of 60 species (51 genera and 38 families) of which 39 species are registered for the first time for Portugal. One new species, Metabelbella epidamaeiformis sp. nov., is described. It is clearly distinguishable from all other species of the genus by the presence of spinae adnatae. An identification key to known Iberian species of Metabelbella is presented. A checklist, the locality and the distribution of all oribatid taxa recorded by us are presented.
doi: 10.1080/01647954.2011.645284doi: 10.1080/01647954.2011.645284The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: checklist; fauna; key; Metabelbella; new species; Oribatida; Portugal; Quercus forests

Morphological and molecular characterisation of a new awl nematode, Dolichodorus mediterraneus sp. n. (Nematoda: Dolichodoridae), from Spain - Jiménez-Guirado, D; Murillo Navarro, R; Liébanas, Gracia; Landa, Blanca B; Castillo, Pablo (Nematology, 2007)
A new species of awl nematode, Dolichodorus mediterraneus sp. n., is described from southern Spain. The new species is described and illustrated by light microscopy and scanning electron microscopy studies from specimens collected in a sandy soil around roots of cork oak (Quercus suber L.) from Hato Raton, Aznalcázar (Seville), southern Spain. Dolichodorus mediterraneus sp. n. is characterised by a prominent, rounded, lip region, which is offset from the body and has four to six very fine annuli; lateral fields areolated with three lines, ending posterior to anus level; tail 72-122 μm long, abruptly tapering to an acuminate, often spicate, terminus; tail projection 51-79 μ m long; spicules ventrally arcuate, 33-42 μm long; gubernaculum slightly ventrally curved, 14-22 μm long. Scanning electron microscopy observations showed a similar en face pattern to other Dolichodorus spp. Molecular data from the ribosomal large subunit D2-D3 expansion segment of 28S rDNA from paratypes yielded a single fragment of approximately 800 bp. This is the first record of the genus Dolichodorus in Spain and only the second in Europe. A key to species is provided.
Keywords: Description; key; morphology; Morphometrics; Ribosomal Large Subunit D2-D3 Region; SEM; taxonomy

Foliar trichomes of the evergreen and semi-deciduous species of the genus Quercus (Fagaceae) in the Iberian Peninsula - LLAMAS, F; PEREZ-MORALES, C; ACEDO, C; PENAS, A (Botanical Journal of the Linnean Society, 1995)
The leaf trichomes of the evergreen and semi-deciduous species of the genus Quercus living in the Iberian Peninsula were studied by means of SEM and LM. The SEM has been particularly useful because of the high quality of the illustrations and the possibility of recognizing the structures under I,M or the stereomicroscope afterwards. The studied species were: Quercus coccifera, Q ilex, Q rotundifolia, Q suber, Q canariensis, Q faginea, Q brateroi and Q lusitanica. All species show some exclusive particularities that permit their identification using these characters. The abaxial surface of the leaf always has more trichomes than the adaxial and hence provides more characters for identification. Quercus alpestris Boiss. shows the same features in the leaf trichomes as Q faginea Lam. A key for identification using these characters is provided.
Keywords: key; leaf; LM; SEM

Foliar trichomes of the evergreen and semi-deciduous species of the genus Quercus (Fagaceae) in the Iberian Peninsula - LLAMAS, F.; PEREZ-MORALES, C.; ACEDO, C.; PENAS, A. (Botanical Journal of the Linnean Society, 1995)
The leaf trichomes of the evergreen and semi-deciduous species of the genus Quercus living in the Iberian Peninsula were studied by means of SEM and LM. The SEM has been particularly useful because of the high quality of the illustrations and the possibility of recognizing the structures under I,M or the stereomicroscope afterwards. The studied species were: Quercus coccifera, Q ilex, Q rotundifolia, Q suber, Q canariensis, Q faginea, Q brateroi and Q lusitanica. All species show some exclusive particularities that permit their identification using these characters. The abaxial surface of the leaf always has more trichomes than the adaxial and hence provides more characters for identification. Quercus alpestris Boiss. shows the same features in the leaf trichomes as Q faginea Lam. A key for identification using these characters is provided.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: key; leaf; LM; SEM